A decision support tool for targeting inland valleys with high potential for agricultural development and biodiversity and ecosystem services preservation - Dossou-Yovo, Elliott Ronald; Akpoti, Komlavi (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Inland valleys are defined as the upper parts of river drainage systems with a complete toposequence from the interfluves to the valley bottom with its seasonally waterlogged depression. Due to their specific hydrological conditions, where the bottom of the valley has predominant water seasonally or throughout the year, inland valleys have a favorable agricultural production, especially for the rice crop. Thus, the inland valleys are considered Africa's future food baskets. While Africa Rice Centre has deployed considerable efforts in characterizing inland valleys ecology in West Africa in recent years, there is still a need to develop actionable maps of inland valleys in terms of the geodatabase and their suitability for rice production in the region. These outputs (geodatabase and suitability) are needed to support project development and implementation for NGOs, and research institutions and to orient government policies aiming at expanding cropland in inland valleys with limited impact on biodiversity and ecosystem services. International Water Management Institute and AfricaRice developed a decision support system to map inland valleys and their potential for agricultural development in Mali using integrated fuzzy-based morphometry multi-scale and ecological niche modeling approach. The integrated approach developed was validated with an accuracy over 90% for both the testing and training datasets. In total, 6,815,205 ha of inland valleys were located, mapped, and characterized using both biophysical and socio-economic variables. Of the total inland valleys area, 802761 ha were mapped as suitable for rice-based systems development, while the remaining 6012444 ha were mapped as suitable for biodiversity and ecosystem services preservation. The tool can be used by the national government, investors, agronomists, and potential land users to identify inland valleys where cropland expansion, sustainable intensification, and ecosystem services preservations could all be feasible.